DYNAMICS PREVALENCE AND INTENSITY OF CHILDREN DENTAL CARIES WITH ACUTE RECURRENT RESPIRATORY VIRAL INFECTIONS IN THE PROCESS OF PROFILACTIC ACTION - L.F. Kaskova; O.S. Pavlenkova (Ukrainian Medical Stomatological Academy, 2017)
Prevention of children dental caries many years remains questionable dental practice both in the world and in Ukraine. Dental status depends of many factors, one of which is the overall health of the child. Acute respiratory viral infections (ARVI), which is one of the global problems of medicine, characterized by high prevalence of this group of diseases among children. According to the state statistical reporting in recent years, every year SARS ill 17, 3-20% of the population. ARVI incidence of 95.1% in the structure of all infectious diseases. The trend to higher incidence of ARVI among children with a prevalence age group 7-14 years, due to the highly contagious in organized groups of children. Therefore, the development and implementation of methods of prevention of children dental diseases, who often suffer from ARVI is an urgent task, which aims to decrease the intensity and prevalence of caries. The aim was to study the dynamics of the prevalence and intensity of children dental caries that often get sick of ARVI during the implementation of preventive measures. Children surveyed were divided into 4 groups of 20 people: Group 1 practically healthy children, who were administered the professional oral hygiene and personal hygiene calcium-containing using toothpaste; 2 - children, who often suffer from acute respiratory viral infection, who were administered the professional oral hygiene and personal hygiene calcium-containing using toothpaste; 3 - children, who often suffer from acute respiratory viral infection, who were administered the professional hygiene twice a year, carrying out individual care using toothpaste "Dragon," the drug "Osteovit" rinsing elixir "Sanodent and addicting drug" Kinder biovital gel "; 4 - children, who often suffer from acute respiratory viral infection, who were administered the professional hygiene twice a year, carrying out individual care using calcium-containing paste application calcium-containing drugs and those that increase the protective properties of the body, "Biotryt C", "Lecithin D3 "rinsing elixir" Lizodent "and the use of the drug" Supervit. " Clinical examination was performed by the method of WHO (1989). This studied prevalence (%) and intensity of caries in terms CPD + KP. Quantitative indicators are statistically processed by the Student- Fisher (r≤0,01). Data on the incidence of ARVI obtained from medical records and by interviewing parents using questionnaires. The effectiveness of the proposed scheme was evaluated at 1 and 6 months after their appointment. Studying the prevalence of caries in children 6-7 years showed relatively high prevalence and intensity of caries process. During one examination prevalence of dental caries was the best in healthy children - 60 ± 11,2%. Children groups sickly, he almost did not differ. During examination 2 rate increase occurred in the 3 groups. At 6 months after the first survey prevalence increased in all study groups. The best among groups of children, who often suffer from ARVI, was the result of 4 groups of children who were administered our proposed way to prevent dental caries - 75 ± 8,66%. The intensity decay was determined in terms of the CPD + kp teeth . During one inspection indicator of the intensity of dental caries was the best in healthy children - 1,95 ± 0,34 tooth. Children groups sickly, he almost did not differ. During the 2 survey was a slight rate increase in all groups of observation. At 6 months after the first survey of prevalence slightly increased in all study groups, but among the best groups of children, who often suffer from ARVI, was the result of 4 groups of children who were administered our proposed way to prevent dental caries, - 3,40 ± 0,58 tooth. This result indicates the increasing resistance of dental hard tissues children often suffer from respiratory virus infections through the use of our proposed complex that covers calcium-containing drug "Lecithin D3", a drug that increases the protective properties of the organism "Biotryt C" multivitamin complex "Supervit "mouthwash" Lizodent "and use kaltsiyumisnoyi toothpaste.